Modelling the impact of drought and heat stress on common bean with two different photosynthesis model approaches. (July 2016) - Seidel, S.J.; Rachmilevitch, S.; Schütze, N.; Lazarovitch, N.
Abstract: Extreme temperature and drought stress are major environmental factors limiting agriculture worldwide. A comprehensive understanding of plant behavior under different environmental conditions can be gained through experiments and through the application of biophysical crop models. This study presents a field experiment conducted with bean exposed to heat and drought stress. Based on an experimental data collection a crop model was set up, calibrated and validated. Hereby, the two different photosynthesis model approaches already implemented in the model, a simple empirical (the Goudriaan and van Laar or GvL model) and a biochemical photosynthesis model approach (the Farquhar-Ball-Collatz or FBC model), were tested. Both photosynthesis model approaches performed adequately under no stress conditions. Under heat stress conditions, yield was underestimated by both models. However, the FBC model performed better than the simpler photosynthesis model approach of the GvL model. The FBC crop model was able to predict the soil water dynamics, the plant growth and the stomatal conductance. Highlights: We tested two different photosynthesis model approaches implemented in a biophysical crop model. A comprehensive experimental data collection was used to set up, calibrate and validate the crop model. The effect of the photosynthesis model choice was evaluated with multiple model runs based on observed data testing several feasible growth and climatic conditions. The application of the Farquhar-Ball-Collatz model implemented in a field-scale crop model is recommended for drought and heat stress simulation studies.